Gas chromatography–mass spectrometry analysis of organic pollutants in French soils irrigated with agro-industrial wastewater - Maurin, Nicolas; Sayen, Stéphanie; Guillon, Emmanuel (Frontiers in Environmental Science, 2023)
The use of agro-industrial wastewater in the agricultural sector is an interesting practice to save resources but it can bring various contaminants to the receiving soils. In this study 19 organic pollutants [8 polycyclic aromatic hydrocarbons (PAH), 6 BTEX, 4-tert-octylphenol, 4-octylphenol, 4-n-nonylphenol, tributyltin and diethylphtalate] were analyzed by gas chromatography-mass spectrometry (GC-MS) in soils irrigated with agro-industrial wastewater from sugar refinery. The soils were sampled at five different locations to evaluate the contamination heterogeneity. Microwave-assisted extraction (MAE) was performed using methanol and hexane and extraction yields ranged from 44% to 96%. The detection limits of the method were between 1.6 and 64 μg·L−1 for polycyclic aromatic hydrocarbons, 0.42 μg·L−1 for diethylphthalate, 0.77 μg·L−1 for tributyltin and until 9.8 μg·L−1 for phenol compounds. The highest contaminant concentrations measured in the soil samples, between 0.4 and 1.2 ng·g−1, were monitored for polycyclic aromatic hydrocarbons molecules, including napthalene, anthracene, fluoranthene, indeno(1,2,3-c,d)pyrene, benzo[a]pyrene, benzo[b]fluoranthene, benzo[k]fluoranthene, and benzo[ghi]perylene. Toluene, ethylbenzene, xylene isomers accounted from 21 to 66 ng·g−1 (mostly toluene). Benzene, 4-tert-octylphenol, 4-octylphenol, 4-n-nonylphenol, tributyltin and diethylphtalate were not detected in soils. The proposed method enables analysis of a wide variety of regulated compounds in a unique preparation step and a unique analytical method. The mean amounts of pollutants were in agreement with measurements or estimates performed in similar contexts.